ANALISIS PERTUMBUHAN EKONOMI DAN PENGEMBANGAN SEKTOR POTENSIAL DI KABUPATEN SIAK - Sri Ayu Kurniati (UIR Press, 2014)
Agriculture is very important for the national economy as a factor of economic growth. The purpose of this research was to analysis the role of agriculture sector to increase of economic growth in Siak Regency and to analyze the strengths, weaknesses, opportunities, and threats in the development of potential sectors in Siak Regency. The research method is a case study of agricultural sector GDP data years 2009-2013 in Siak Regency. The analysis used is Location Quotient (LQ) and SWOT. LQ analyze showed that the Siak Regency had three potential sub-sectors, namely food crops, plantations, and fishing for LQ value greater than one. Food crop subsector had the highest LQ values with an average of 1.58 per year. Strategies to empower potential sectors in Siak Regency are strategy strenghts-Opportunities (S-0) with using the internal strength to take advantage of external opportunities in order to gain benefit in development and economic growth Siak Regency. Namely improving the way in which natural resources are owned by sector basis, increasing the system of alliances and partnerships with various stakeholders, and to optimize the coordination of the various parties in increasing agricultural production.